Exploring existing drugs: proposing potential compounds in the treatment of COVID-19 - Kabir, Eva Rahman (Heliyon, 2021)
The COVID-19 situation had escalated into an unprecedented global crisis in just a few weeks. On the 30(th) of January 2020, World Health Organization officially declared the COVID-19 epidemic as a public health emergency of international concern. The confirmed cases were reported to exceed 105,856,046 globally, with the death toll of above 2,311,048, according to the dashboard from Johns Hopkins University on the 7(th) of February, 2021, though the actual figures may be much higher. Conserved regions of the South Asian strains were used to construct a phylogenetic tree to find evolutionary relationships among the novel virus. Off target similarities were searched with other microorganisms that have been previously reported using Basic Local Alignment Search Tool (BLAST). The conserved regions did not match with any previously reported microorganisms or viruses, which confirmed the novelty of SARS-CoV-2. Currently there is no approved drug for the prevention and treatment of COVID-19, but researchers globally are attempting to come up with one or more soon. Therapeutic strategies need to be addressed urgently to combat COVID-19. Successful drug repurposing is a tool that uses old and safe drugs, is time effective and requires lower development costs, and was thus considered for the study. Molecular docking was used for repurposing drugs from our own comprehensive database of approximately 300 highly characterized, existing drugs with known safety profile, to identify compounds that will inhibit the chosen molecular targets - SARS-CoV-2, ACE2, and TMPRSS2. The study has identified and proposed twenty seven candidates for further in vitro and in vivo studies for the treatment of SARS-CoV-2 infection.